Preterm birth risk in mother with hypertensive disorders of pregnancy - Muh. Amri Arfandi; Ansariadi Ansariadi; Ridwan Amiruddin; Wahiduddin Wahiduddin; Andi Ummu Salmah; Abdul Salam (Intelektual Pustaka Media Utama, 2023)
Preterm birth (PTB) is a major public health concern and is the leading cause of under-5 child mortality. Some studies suggest that hypertension disorders of pregnancy (HDP) play an important role in causing PTB. HDP is a term that includes chronic hypertension (CH), gestational hypertension (GH), and pre-eclampsia (PE). The association between the various types of HDP and PTB has not been studied specifically in prior research, yet. Therefore, the purpose of this study is to analyze risk differences among HDP types. This study was carried out in Makassar's Maternal and Child Hospital using a case-control study design. A sample consisting of 138 cases and 276 controls was collected from the medical record data. Odds ratio and logistic regression test analysis were used to obtain both crude OR (COR) and adjusted OR (AOR). The finding shows that regardless of its type, HDP is a major risk factor for preterm birth. The findings also indicated that PTB risk differs depending on the type of HDP suffered. CH had the highest risk (COR=5.61; AOR=6.58), followed by PE (COR=3.36; OR=3.18) and GH (COR=3.46; AOR=3.09), which have fairly similar risks. CH which has the greatest risk needs to be considered to be the focus of prevention. While in the context of preventing preterm delivery, GH and PE need to receive the same attention. However, prevention and treatment must still be adjusted depending on the type of hypertension suffered.